Development of Edutainment-Based Interactive E-Modules Physics in Class XII - Yusuf, Mokhammad; Mustaji, Mustaji; Fatir, A. Noor (EDUCATIO : Journal of Education, 2023)
The learning process is fundamentally a communication process within education. Media's role is crucial, as it aids in clarifying ambiguous material and acting as an intermediary. Complex subjects can be simplified using media, addressing teacher limitations in conveying concepts and solidifying abstract material. Developing Edutainment-Based Interactive E-Modules for Class XII Physics at SMA Negeri 1 Bluluk enables teachers to innovate, creating engaging content. Students benefit from active participation in collaborative learning, both online and offline, facilitated by Canva for Education. This study employs the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) for development, utilizing questionnaires for material, learning design, and media experts. Trials involving peer, individual, small group, and field testing were conducted among teachers and students. The feasibility of the learning media was positively assessed by experts, yielding high percentages. Validation of Canva for Education Technology-Based Learning Media indicated its suitability for Physics education in Class XII at SMA Negeri 1 Bluluk Lamongan.